2013
DOI: 10.1038/srep03120
|View full text |Cite
|
Sign up to set email alerts
|

ABCC3 as a marker for multidrug resistance in non-small cell lung cancer

Abstract: Multidrug resistance (MDR) contributes to the failure of chemotherapy and high mortality in non-small cell lung cancer (NSCLC). We aim to identify MDR genes that predict tumor response to chemotherapy. 199 NSCLC fresh tissue samples were tested for chemosensitivity by MTT assay. cDNA microarray was done with 5 samples with highest resistance and 6 samples with highest sensitivity. Expression of ABCC3 mRNA and protein was detected by real-time PCR and immunohistochemisty, respectively. The association between g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 24 publications
2
32
0
Order By: Relevance
“…11L and 4R showed higher expression level (> 14 fold change) of ABCC3 gene than primary (< 8-fold). ABCC3 has been known to be a marker for multidrug resistance in NSCLC (39). Furthermore, pathway alterations according to aberrant gene expression could confer drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…11L and 4R showed higher expression level (> 14 fold change) of ABCC3 gene than primary (< 8-fold). ABCC3 has been known to be a marker for multidrug resistance in NSCLC (39). Furthermore, pathway alterations according to aberrant gene expression could confer drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…S6). Many of these transporters including ABCG2, ABCC3, and lung cancer resistance protein (LRP) have previously been implicated in gemcitabine resistance and/or are highly expressed in pancreatic tumors (23,25,26). Expression levels of the monocarboxylate transporter (SLC3A2), the antigen peptide transporter (TAP2), and an amino acid transporter (SLC16A1) were mildly increased (twofold to fourfold, P < 0.05) in Panc02.13 expressing the YAPS6A construct (Fig.…”
Section: Cell-cell Contact-dependent Response To Gemcitabine In Pancrmentioning
confidence: 99%
“…One can speculate that such effect is caused by a toxicity of oMWCNTs-PEG; nevertheless, our data illustrated that the exposure to oMWCNTs-PEG alone did not cause any effect on the viability of both the cell lines up to 72 h, and thus the nanoparticles were proven to be highly biocompatible. We hypothesize that the utilization of oMWCNTs-PEG for VP-16 delivery specifically allow for an uptake through the endocytosis as was shown by Lee and coworkers [35], bypassing the P-gp efflux pump and reducing in P-gp dependent multidrug resistance properties, which can be a co-factor of NSCLC chemoresistance [36]. The significant knock-down effects, obtained after the treatments with oMWCNTs-PEG-VP-16-Aso confirmed that the design of Aso for specific binding to the first six codons of the human Bcl-2 mRNA induced the satisfactorily decrease in Bcl-2 protein translation [37].…”
Section: Discussionmentioning
confidence: 91%